Crossover and noncrossover recombination during meiosis: timing and pathway relationships. - Storlazzi, A (1995)
During meiosis, crossovers occur at a high level, but the level of noncrossover recombinants is even higher. The biological rationale for the existence of the latter events is not known. It has been suggested that a noncrossover-specific pathway exists specifically to mediate chromosome pairing. Using a physical assay that monitors both crossovers and noncrossovers in cultures of yeast undergoing synchronous meiosis, we find that both types of products appear at essentially the same time, after chromosomes are fully synapsed at pachytene. We have also analyzed a situation in which commitment to meiotic recombination and formation of the synaptonemal complex are coordinately suppressed (mer1 versus mer1 MER2++). We find that suppression is due primarily to restoration of meiosis-specific double-strand breaks, a characteristic of the major meiotic recombination pathway. Taken together, the observations presented suggest that there probably is no noncrossover-specific pathway and that restoration of intermediate events in a single pairing/recombination pathway promotes synaptonemal complex formation. The biological significant of noncrossover recombination remains to be determined, however.